Kinetics and Mechanism of Oxidation of Some Primary Alcohols by N-Bromobenzamide - Siriah, V.K.; Mohan Gupta, Naresh (Asian Journal of Chemistry, 2010)
Kinetic studies in the oxidation of n-butyl alcohol and amyl alchohol with N-bromobenzamide has been made in aqueous acetic acid in presence of mercuric acetate. The reaction is fIrst order, each with respect to oxidant and substrate. Order with respect to perchloric acid is fractional or fIrst order depending upon the substrate concentration. Suggest protonation of the substrate in course of reaction. A mechanism consistent with the result has been proposed.